PENGARUH WILAYAH BEBAS KORUPSI (WBK) TERHADAP KINERJA PEGAWAI DI KEJAKSAAN NEGERI JENEPONTO - Sulfina, Ayu; Adys, Abdul Kadir; Mustari, Nuryanti (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study was to understand corruption-free areas and the performance of employees at the Jeneponto District Attorney's Office. This study of research is quantitative with a sample of 48 people. The results of the study indicate that a corruption-free area has a strong influence on the performance of employees at the Jeneponto. Based on the output of the summary model, the results obtained by R are as large as the contribution of the X variable affecting the Y variable, the influence is symbolized by R (regression). The magnitude of the regression value or influence (R) is 0.651, which means 65.1%. The influence of the independent variable or corruption-free area (X) on the dependent variable or employee performance (Y) which is also strengthened by the value of the coefficient of determination (R²/R squer) or the determinant coefficient of 0.424, meaning 65.1%. The influence of the independent variable or corruption-free area (X) on the dependent variable or employee performance has an influence of 65.1% while 34.9% is influenced by other factors.